Evaluasi Usability pada Aplikasi E-LPPD Provinsi Jawa Timur menggunakan Metode Heuristic Evaluation dan Usability Testing - Salviko Israfi Talanrea; Satrio Hadi Wijoyo; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In the context of implementing e-Government in the application of Government Regulation Number 13 of 2019 concerning Reports and Evaluation of Regional Government Implementation in the implementation of regional autonomy policies as a whole. The Bureau of Government and Regional Autonomy, the Regional Secretariat of East Java Province, operates a web-based application for online delivery of Local Government Implementation Reports. Evaluation is needed on the application service as an improvement in the quality of the application at a later stage. This study aims to develop these services, especially in the usability section and to design interfaces as recommendations for usability improvements. This study uses the Heuristic Evaluation and Usability Testing method which involves 5 users and 3 experts in the usability field. The Heuristic Evaluation Method consists of 17 heuristic problems which are divided into 1 cosmetic problem, 6 minor problems, 6 major problems, and 4 disaster problems. The Usability Testing method was carried out in 2 stages in the test, the test was carried out before and after the arrival of the user interface, it was found that the test increase from the third aspect tested, namely the effectiveness aspect with an initial value of 86% to 88% efficiency aspect with a value of 81.3% to 84, 08% and satisfaction with the initial value of 72.5% to 79%.